An Assessment of Challenges and Professional Development Needs of Tour Guides in Sri Lanka - Indrachapa Gunasekara (Goodwood Publishing, 2026)
Purpose: The main objective of the research is to examine the key challenges face by tour guides in Sri Lanka with the development of tourism Methodology: This research utilized a mixed research design that combined quantitative and qualitative approaches. The quantitative approaches were selected to identify the patterns of challenges faced by the tour guides while qualitative approaches made for the deeper insight about the experiences and tour guides’ perceptions Results: The development of professionalism and job satisfaction of tour guides in Sri Lanka is identified in five areas: welfare of the tour guides, job security, financial stability, knowledge development, and social recognition. Conclusions: The challenges faced by tour guides in the Sri Lankan tourism industry have been identified as key challenges. Corrective measures were introduced for the identified areas. Limitations: Lack of registered tour guides and inconvenience in accessing the population of registered tour guides due to the nature of the profession. Contributions: This study contributes to the establishment of professionalism and job satisfaction among tour guides in Sri Lanka. The study’s main contribution is to policy makers, service providers, and the general societal acceptance of the tourist guide profession.